Exact analytical Taub-NUT like solution in f(T) gravity - Joshua G. Fenwick; Masoud Ghezelbash (European Physical Journal C: Particles and Fields)
Abstract We construct exact analytical Taub-NUT solutions in the context of f(T) gravity. We study the physical properties of the solutions, and compare them with those of the Taub-NUT solution in Einstein gravity.